Media Literacy Siswa Muslim Surabaya dalam Penggunaan Internet - Santoso, Agus (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2015)
This article discusses about media literacy of the senior high school students using internet facility to search, acces, and evaluate information or everything they need as well as how they communicate the information. Population of this research is senior high school students in Al Hikmah Surabaya. The depiction of the student’s media literacy will be analised based on their personal and social competence. Models of media literacy that become references in this research are Individual Competences Framework by European Commision, Grade of media literacy by Fedorov, ICT Literacy by Katz, and other model information behavior from Ellis, and Dervin. The result shows that in terms of personal competence the student’s media literacy classified at the level of media literacy medium type while in social compe–tence the level of their media literacy is in advance type.